ANALISIS VARIABEL KARAKTER PENGUSAHA YANG BERPENGARUH TERHADAP KINERJA USAHA INDUSTRI KECIL MAKANAN RINGAN DI KOTAMADYA MALANG - Muniroh, Muniroh (Akutansi Bisnis & Manajemen ( ABM ), 2003)
One the one hand, the existence of small-scale industry in Indonesia is perceived as an unprofessional industry, managed by people with limited skills and implementing traditional technology. On the other, small-scale industry can be viewed as an activity capable of uplifting the economy of small people and having positive impact in the terms of the ease to penetrate. This condition is very strategic for the growth and equal distribution of economy in Indonesia, which has a big population with low average educational background. The contribution of this sector is still considered very insufficient for the rapid population growth. Therefore, professional small-scale industry is paramount. However, the constraints of insufficient human resources quality, slow market development, lack of capital, and limited technology and management are evident. This study is aimed at determining the variables influencing the caracter of manager, snack food processing industries in particular. The study results are expected to contribute information about dominant variables influencing the improvement of performance of small-scale industry bussinessmen. The study employed six independent variables, the age, marital status, number of dependents, experience, the entrepreneur mental attitude and employee turn over. On the other hand, the dependent variable was the contribution income used as a performance measurement variable. Number of samples was used 50 the entrepreneur of small-scale industry in Malang, and with non proportional stratified sampling. The results of the study indicate the following 1) Simultaneously, the six independent variables significantly influenced the company performance with the determination coefficient stood at 35,5 %, whereas partially, the four variables of age, experience and the entrepreneur mental attitude significantly influenced the company performance with a significance level of a = 10 %. 2) Age was the variable with dominant influence on the company performance.